Comparative microscopic and molecular analysis of Thatcher near‐isogenic lines with wheat leaf rust resistance genes Lr2a, Lr3, LrB or Lr9 upon challenge with different Puccinia triticina races. (16th July 2012) - Wang, X.; McCallum, B. D.; Fetch, T.; Bakkeren, G.; Marais, G. F.; Saville, B. J.
<x xml:space="preserve">Abstract</x> Thatcher near‐isogenic lines (NILs) of wheat carrying resistance gene Lr2a, Lr3, LrB or Lr9 were inoculated with Puccinia triticina races of virulence phenotype BBBD, MBDS, SBDG and FBDJ. Puccinia triticina infection structures were analysed under the fluorescence microscope over a course of 14 days after inoculation (dai). The relative proportion of P. triticina and wheat genomic DNA in infected leaves was estimated with a semiquantitative multiplex PCR analysis using P. triticina‐ and wheat‐specific primers. The occurrence of a hypersensitive response (HR), cellular lignification and callose deposition in inoculated plants was investigated microscopically. In interactions producing highly resistant infection type (IT) '0;', a maximum of two haustorial mother cells per infection site were produced, and there was no increase in the proportion of P. triticina genomic DNA in infected leaves, indicating the absence of P. triticina growth. In comparison, sizes of P. triticina colonies increased gradually in interactions producing moderately resistant IT '1' and '2', with the highest proportion of P. triticina genomic DNA found in leaves sampled at 14 dai. In interactions producing susceptible IT '3–4', the highest proportion of P. triticina genomic DNA was found in leaves sampled at 10 dai (45·5–51·5%). HR and cellular lignification were induced in interactions producing IT '0;' and '1' at 1 dai but they were not observed in interactions producing IT '2' until 2 dai. No HR or cellular lignification were induced in interactions producing susceptible IT '3–4'. Furthermore, a strong deposition of callose was induced in Lr9 + BBBD and Lr9 + FBDJ (IT '0;'), whereas this defence response was not induced in resistant or susceptible interactions involving Lr2a, Lr3 or LrB, indicating that Lr9 mediated resistance was different from that conditioned by Lr2a, Lr3 or LrB.